PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN POWERPOINT INTERAKTIF TERHADAP PEMAHAMAN KONSEP SISWA - Zanuba, Saskia Asha; Sidik, Rahmad Fajar; Qomaria, Nur; Astid Putra, Dwi Bagus Rendy; Sutarja, Maria Chandra (Natural Science Education Research, 2026)
The purpose of this study was to determine the difference in the increase in students' conceptual understanding between the control class using a conventional learning model (lecture) and the experimental class using a guided inquiry learning model assisted by interactive powerpoint on the material of the earth and the solar system. The study was conducted at the UPTD SMPN 1 Bangkalan school on grade VII students in the even semester of the 2024/2025 academic year. The sample used in this study were grade VII-B students as the control class and grade VII-C students as the experimental class. The results showed that there was a difference in the average posttest score between the control class and the experimental class. In the hypothesis test, the posttest results used the non-parametric Mann Whitney U test with a sig. (2 tailed) of 0,000 which is smaller 0,05 which means H0 is rejected and H1 is accepted. And there was an increase in conceptual understanding on the material of the earth and the solar system with an average N-Gain value of 0,58 which is included in the moderate criteria. So it can be concluded that there is an influence of the guided inquiry model assisted by interactive powerpoint on students' conceptual understanding